UKRAINIAN REGISTRY ACUTE CORONARY SYNDROMES WITH ST SEGMENT ELEVATION «STIMUL»: RISK PREDICTING MODEL OF IN-HOSPITAL MORTALITY - Valueva, S.V. (World of Medicine and Biology, 2013)
In this article we discuss the process of development of risk predicting model of in-hospital mortality at patients with acute coronary syndromes with ST segment elevation derived from the Ukrainian registry «STIMUL». This model uses the weighted risk score being derived from a summation based on the presence or absence of 9 adverse risk factors were advanced age, higher Killip class, lower systolic blood pressure and haemoglobin, higher heart rate and serum creatinine, not having reperfusion, elevated serum cardiac markers (≥ 8 ng/dl), history of heart failure. A risk predicting model validate in-hospital mortality on low (1 %; ≤ 6,5 points), middle (4 - 5 %; 7 – 11,5 points), high (25 - 30 %; 12 – 16,5 points) and very high risk score (≥85%; ≥17 points). This model found to have a good discrimination among pts with STEMI (c-statistic = 0,94).
Keywords: acute coronary syndromes; survey; risk predicting model of in-hospital mortality; Ukraine